Evaluating Accessibility of Mobile Phone Technology (mHealth Platform) on Maternal and Child Health Care - Christopher Andere Agwenyi; Alice Nambiro Wechuli (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
ICT has revolutionized the healthcare sector by enabling remote patient monitoring, teleconsultation, electronic health records (EHR), mobile health (mHealth), and telemedicine services. This study evaluates the accessibility of Mobile Phone Technology, an mHealth platform designed to complement medical facilities in rural and underserved communities, thereby improving maternal and child health (MCH) outcomes. By leveraging the existing social connections of new mothers and pregnant women-such as parents, siblings, friends, neighbors, spouses, and community health volunteers-the platform facilitates access to crucial healthcare services beyond prenatal and antenatal care.